2010
DOI: 10.1038/ncomms1004
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-regulated vinyl copolymers by metal-catalysed step-growth radical polymerization

Abstract: Proteins and nucleic acids are sequence-regulated macromolecules with various properties originating from their perfectly sequenced primary structures. However, the sequence regulation of synthetic polymers, particularly vinyl polymers, has not been achieved and is one of the ultimate goals in polymer chemistry. In this study, we report a strategy to obtain sequenceregulated vinyl copolymers consisting of styrene, acrylate and vinyl chloride units using metalcatalysed step-growth radical polyaddition of design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
166
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(171 citation statements)
references
References 30 publications
2
166
0
Order By: Relevance
“…Kamigaito and coworkers used a metal catalyzed stepgrowth radical polyaddition to obtain sequence regulated vinyl copolymers, consisting of styrene, acrylate, and vinyl chloride units. [21] The resulting segmented polymers had within each segment a defined ABCC-sequence of vinyl chloride-styrene-acrylate-acrylate monomers. Lutz et al suggested a highly innovative strategy to establish positional control of functional entities within linear high-molecular-weight polymers.…”
Section: Detours Via Monomer Sequence-controlled Polymersmentioning
confidence: 99%
“…Kamigaito and coworkers used a metal catalyzed stepgrowth radical polyaddition to obtain sequence regulated vinyl copolymers, consisting of styrene, acrylate, and vinyl chloride units. [21] The resulting segmented polymers had within each segment a defined ABCC-sequence of vinyl chloride-styrene-acrylate-acrylate monomers. Lutz et al suggested a highly innovative strategy to establish positional control of functional entities within linear high-molecular-weight polymers.…”
Section: Detours Via Monomer Sequence-controlled Polymersmentioning
confidence: 99%
“…[5,13,15,20,[22][23][24][25][26][27][28][29][30][31][32] In particular, a few research groups investigated sequence-regulation in chaingrowths polymerizations. For instance, the innovative approaches recently reported by the research groups of Sawamoto, [26,29,32,33] Thomas, [10,27] and Kamigaito [20,30] have to be mentioned. In parallel, our research group studied the controlled radical chain-growth copolymerization of ultra reactive comonomers.…”
Section: Introductionmentioning
confidence: 99%
“…Nature's precision in regulating monomer sequences also remains unmatched in non-natural macromolecules [6][7][8][9][10] . Among the various examples of sequence-regulated synthetic macromolecules, block copolymers exhibiting a large number and type of functional sequences -that is, multiblock copolymers-are unique and original structures that exhibit a type of primary structure (although the sequence control is typically limited by the monomer distribution within each block).…”
mentioning
confidence: 99%